Community structure and photosynthetic physiology of phytoplankton in the northwest subarctic Pacific during an in situ iron fertilization experiment (SEEDS-II) - Suzuki, Koji; Saito, Hiroaki; Isada, Tomonori; Hattori-Saito, Ai; Kiyosawa, Hiroshi; Nishioka, Jun; McKay, R. Michael L.; Kuwata, Akira; Tsuda, Atsushi (Deep Sea Research Part II: Topical Studies in Oceanography, 2009)
Temporal changes in the abundance, community composition, and photosynthetic physiology of phytoplankton in surface waters were investigated during the second in situ iron (Fe) fertilization experiment in the NW subarctic Pacific (SEEDS-II). Surface chlorophyll a concentration was 0.75 mg m-3 on the day before the first Fe enrichment (i.e. Day 0), increased ca. 3-fold until Day 13 after two Fe additions, and thereafter declined with time. The photochemical quantum efficiency (Fv/Fm) and functional absorption cross-section (σPSII) of photosystem II for total phytoplankton in surface waters increased and decreased inside the Fe-enriched patch through Day 13, respectively. These results indicate that the photosynthetic physiological condition of the phytoplankton improved after the Fe infusions. However, the maximum Fv/Fm value of 0.43 and the maximum quantum yield of carbon fixation (φmax) of 0.041 mol C (mol photon)-1 during the development phase of the bloom were rather low, compared to their theoretical maximum of ca. 0.65 and 0.10 mol C (mol photon)-1, respectively. Diatoms, which were mainly composed of oceanic species, did not bloom, and autotrophic nanoflagellates such as cryptophytes and prasinophytes became predominant in the phytoplankton community inside the Fe-enriched patch. In ferredoxin/flavodoxin assays for micro-sized (20-200 μm in cell length) diatoms, ferredoxin was not detected but flavodoxin expressions consistently occurred with similar levels both inside and outside the Fe-enriched patch, indicating that the large-sized diatoms were stressed by Fe bioavailability inside the Fe-enriched patch even after the Fe enrichments. Our data suggest that the absence of a Fe-induced large-sized diatom bloom could be partly due to their Fe stress throughout SEEDS-II. © 2009 Elsevier Ltd. All rights reserved.